Successful Use of Renal Denervation in Patients With Loin Pain Hematuria Syndrome—The Regina Loin Pain Hematuria Syndrome Study - Prasad, Bhanu (Kidney Int Rep, 2018)
INTRODUCTION: Loin pain hematuria syndrome (LPHS) is characterized by severe unilateral or bilateral loin pain that suggests a renal origin but occurs in the absence of identifiable or relevant urinary tract disease. Hematuria can either be microscopic or macroscopic, but the renal abnormalities responsible for the hematuria are unexplained. Debilitating pain refractory to conventional pain medications is the main cause of morbidity. METHODS: We conducted a single-arm, single-center study. Twelve patients between the ages of 21 and 62 years (11 female, 1 male) with LPHS underwent endovascular ablation of the renal nerves between July 2015 and November 2016, using the Vessix renal denervation system. The primary objective was to achieve 30% reduction in self-reported pain with the McGill Pain Questionnaire (MPQ) at 6 months. The secondary objectives were to measure changes in disability (Oswestry Disability Index [ODI]), mood (Geriatric Depression Scale [GDS]), and quality of life (EuroQol-5D [EQ-5D] and the MOS 36-Item Short Form Survey [SF-36]) scores from baseline to 6 months postprocedure. RESULTS: Ten of 12 patients at 3 months and 11 of 12 patients at 6 months reported a >30% reduction in pain based on the MPQ at 3 and 6 months. We found consistent improvements in MPQ, ODI, GDS, EQ-5D, and SF-36 scores from baseline to 6 months postprocedure. CONCLUSION: We conclude that renal denervation is associated with a considerable improvement in pain, disability, quality of life, and mood. Our results suggest that percutaneous catheter−based delivery of radiofrequency energy is a safe, rapid treatment option that should be considered in all patients with LPHS.